2021
DOI: 10.3390/microorganisms9091911
|View full text |Cite
|
Sign up to set email alerts
|

What WGS Reveals about Salmonella enterica subsp. enterica in Wildlife in Germany

Abstract: The aim of this study was to gain an overview of the genetic diversity of Salmonella found in wildlife in Germany. We were particularly interested in exploring whether wildlife acts as a reservoir of certain serovars/subtypes or antimicrobial resistance (AMR) genes. Moreover, we wanted to explore the potential of Salmonella in spreading from wildlife to livestock and humans. To answer these questions, we sequenced 260 Salmonella enterica subsp. enterica isolates sampled between 2002 and 2020 from wildlife acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
(83 reference statements)
2
10
0
Order By: Relevance
“…Our course-grained epidemiological investigation of Salmonella from various sources in southern Ontario has provided insights into potential transmission between these different sources, and provides further evidence that, although raccoons have the potential to disseminate Salmonella and AMR to humans, their contribution appears to be minimal. Our findings build on existing work suggesting that wildlife play a largely indirect role in the transmission of Salmonella, serving primarily as biological intermediaries between humans, livestock and the environment, rather than acting as a primary driver or major reservoir (40)(41)(42)(43)(44). The identification of highly similar or identical cgMLST types (<10 allelic differences) was a rare occurrence in this population of over 600 isolates and was very specific to certain sources and serovars, highlighting potential transmission only in certain contexts (i.e., S. Heidelberg between poultry and humans, S. Newport between raccoons and soil).…”
Section: Discussionsupporting
confidence: 78%
“…Our course-grained epidemiological investigation of Salmonella from various sources in southern Ontario has provided insights into potential transmission between these different sources, and provides further evidence that, although raccoons have the potential to disseminate Salmonella and AMR to humans, their contribution appears to be minimal. Our findings build on existing work suggesting that wildlife play a largely indirect role in the transmission of Salmonella, serving primarily as biological intermediaries between humans, livestock and the environment, rather than acting as a primary driver or major reservoir (40)(41)(42)(43)(44). The identification of highly similar or identical cgMLST types (<10 allelic differences) was a rare occurrence in this population of over 600 isolates and was very specific to certain sources and serovars, highlighting potential transmission only in certain contexts (i.e., S. Heidelberg between poultry and humans, S. Newport between raccoons and soil).…”
Section: Discussionsupporting
confidence: 78%
“…Salmonella is a genus of the family Enterobacteriaceae. Taxonomically, this genus is separated into two species: Salmonella bongori and Salmonella enterica, which contain six subspecies with serovars like Salmonella Typhi, Salmonella Enteritidis, Salmonella Paratyphi, Salmonella Typhimurium, and Salmonella Choleraesuis [1].Salmonella enterica causes typhoidal and nontyphoidal salmonellosis (NTS) [2]. Te WHO estimates the global typhoid fever disease burden at 11-20 million cases annually, resulting in about 128 000-161 000 deaths per year [3].…”
Section: Introductionmentioning
confidence: 99%
“…While we isolated Y. enterocolitica from 12 out of 77 samples, only one strain isolated from a raccoon harboured the known virulence plasmid and can thus be considered pathogenic. Salmonella Choleraesuis ST‐145 is mainly found in wild boar but has also been reported in foxes in Germany by Uelze et al ( 2021 ). Interestingly, Uelze et al also reported that aminoglycoside resistance genes and ciprofloxacin resistance conferring mutations, which were however, different from the gene and mutation detected in our strain.…”
Section: Discussionmentioning
confidence: 81%
“…Other pathogens such as Salmonella enterica subsp. enterica (Uelze et al, 2021 ), Yersinia enterocolitica (Carella et al, 2022 ) and Listeria spp. (Nowakiewicz et al, 2016 ) have been reported from predators, but their genomic sequences are largely missing so far, making comparisons to human isolates difficult.…”
Section: Introductionmentioning
confidence: 99%